The Eurodollar bond market - Fisher, Frederick G. (London : Euromoney Publications, 1979)
This book is intended as a general introduction to the Eurodollar bond market. It is addressed primarily to newcomers to this market, trainee bankers and prospective investors. Its chief objective is to outline the way business is carried on in market. A second objective of the book is to describe the functioning of the market in such a way as to clarify misconceptions or misunderstandings about its role.
Includes bibliographical references: p. 198 and index.
ne 22/01/2019
Loans
Keywords: Euro-bond market; Bond market